The outgassing rate of titanium-aluminium alloys - Edelmann, Christian (Vacuum, 1992)
The outgassing rates of the Soviet titanium alloys WT 20 and OT 4-1 were measured with a throughput method. The construction of the all-glass uhv apparatus with mercury diffusion pumps is described in detail. After 1 h of pumping at a temperature of 573 K the specific outgassing rate of the alloy WT 20 is of the order of magnitude of 10 −6 Pa l s cm −2. The exact value depends essentially on the pretreatment and on the temperature. The alloy OT 4-1 has at 50°C a somewhat higher specific outgassing rate of about 4 × 10 −6 Pa l s cm −2. Both materials can be used for the construction of uhv devices.